Perspectives on life following a traumatic spinal cord injury. Issue 3 (July 2021) - Hall, Allyson G.; Karabukayeva, Aizhan; Rainey, Carmen; Kelly, Reena J.; Patterson, Jonathan; Wade, Jamie; Feldman, Sue S.
Abstract: Background: Persons living with traumatic Spinal Cord Injury (SCI) face challenges when returning to their communities. The Spain Rehabilitation Center at the University of Alabama at Birmingham is developing a continuum of care for SCI patients. The perspectives of individuals with SCI are critical to designing a person-centered approach to the continuum. Objective: This study sought to explore the lived experiences of individuals with SCI after their injury, as well as obtain the perspectives of therapists working with SCI patients. Methods: Ten persons ranging in age from 23 to 65 years old and living with SCI were recruited to participate in in-depth interviews. We utilized a grounded theory approach to develop descriptive codes and themes. Results: Our analysis highlighted domains that are critical to the lives of individuals with SCI including: planning for life after SCI, intrinsic motivation, environmental barriers, financial barriers, role of family, friends, and social networks, and relationships with medical providers. A key theme was the need for more information about how to manage their health condition, including the development of plans that are tailored to their specific needs. Conclusions: Individuals with an SCI need access to a continuum of care that addresses both medical and social needs.